Program of technological rehabilitation nursing - Rodrigues, Elsa (2021)
+P.E.R.T.O., aims to implement a digital rehabilitation program, accompanied by a communication and monitoring channel, via APP, for eligible users and caregivers to join. +P.E.R.T.O. has 4 fundamental sections: 1- Exercise program aimed at rehabilitation: • Phase 1 – preoperative (preparation), • Phase 2 – hospitalization, • Phase 3 – post-operative (recovery). 2- Useful information section with feedback system. 3- On-time monitoring and follow-up section. 4- Section ‘‘ talk to the rehabilitation nurse ’’, a communication channel that it also allows to assist the user and caregiver in decision making in aspects such as: pain, edema and surgical wound.